Análise da eficiência técnica das redes hospitalares públicas estadual e municipal em Fortaleza - Gondim, Sócrates Santos (2008)
The aim of the present work is to search for parameters which will allow the evaluation of the relative technical efficiency in fourteen state as well as municipal public hospitals located in Fortaleza in the year 2006. It was used the methodology (Data Envelopment Analysis-DEA) aiming to subsidize the manager's decisions attending the principle of efficiency inscribed in the article 37 of the Federal Constitution of Brazil. It was used in the research, the original models CCR (Charne, Cooper and Rhodes) and CCR-O and in their applications we used the software DEA- Solver for the identification of the DMU’s (Decision Making Units) which are at the border of production. The process of disintegration of the five inputs and four outputs, researched here, enabled us to work with the two empiric models and both scenarios and a bigger number of units of the district, reached the border of production. It is important to highlight that, as far as a hospital is concerned, the fact of having 100% of relative productivity, its excellent performance is only effective in the context analyzed. In summary, the Data Envelopment Analysis-DEA evidenced efficiency in the object of the research, as we compared similar unities and established efficiency standard for the hospital of the Unique Health System (SUS).